OPTICAL EVALUATION OF 3D PRINTED CPC BY COUPLING PHOTOGRAMMETRY AND RAY TRACING ANALYSIS - Martínez-Manuel, Pedro R.; Valentín-Coronado, Luis M.; Salgado-Transito, Iván; Peña-Cruz, Manuel I.; Martell-Chávez, Fernando; Carrillo-Baeza, J. Gonzalo; Pineda-Arellano, Carlos A. (Journal of Applied Engineering Science, 2022)
Manufacturing methods of CPC collectors, regardless the application, have not undergone significant modifications in recent years; the main manufacturing methods are hydraulic press stamping and some other machining methods, which generate errors in geometric curvature and damage to the high-reflectivity film coating, reducing the overall optical efficiency of the CPC. In this work, we propose a method for the fabrication of cylindrical CPCs (widely used in water-heating, disinfection, and wastewater treatment applications), which comprises the use of a 3D printed mold complemented with a structural styrofoam molding. The proposed method presents the advantage of improving the quality of the CPC profile with less damage on the surface of the high reflectivity coating and with a reduction in the quantity of deformations because of its machining processes. To evaluate the effectiveness of the presented method, an experimental-simulation test was carried out based on a photogrammetric technique combined with a Ray tracing Monte Carlo method. The test procedure compared the CPC manufactured with the proposed method (called 3DM-CPC) versus one manufactured by a conventional machining technique (referred as CM-CPC). The results obtained show a geometrical mean error value of 1.2 mm for the 3DM-CPC compared to 3.19 mm for the CM-CPC. Optical assessment by ray tracing showed a relative efficiency of 95% for the 3DM-CPC versus 82% of the CM-CPC, both of them compared to the theoretical ideal geometry of a 2D-1 Sun CPC. The benefit could be estimated in a simulation to be 9.4% in the annual performance of a 1000 L CPC thermal energy solar plant.
Keywords: CPC manufacturing, 3D printed molds, photogrammetric technique, photocatalytic reactor, solar concentrator